Invasion stages of Pterygoplichthys spp. (Pisces: Loricariidae) in the Luzon Island, Philippines - Chavez, Joel M. (Animo Repository, 2014)
Species invasion was identified as one of the main factors in biodiversity loss and it has been the subject of multilateral agreements among countries under the Convention of Biological Diversity to protect the natural environment. One of the more cryptic but potentially devastating invasion events of recent times in the Philippines is the one caused by species of Pterygoplichthys or locally known as janitor fish. In this paper, we provide an appraisal of this invasion event in several areas we surveyed were Pterygoplichthys spp. has been introduced. We performed: 1) a taxonomic survey of collected Ptmygoplichthys specimens in localities in the Luzon Island; 2) an ecological survey of waterways in the localities; and 3) field interviews of peopl e during the visits. Our results show that the eight sites visited have been invaded by Pterygoplichthys spp. Invasion stages range from Stage II to Stage V. The invasion situation at each site is discussed. In this paper, we also offer insights on a multiple founding event for Pterygoplichthys spp., as well as its implications to local policies on management and mitigation on species invasions.